Растительноядные виды рода Eurytoma Illiger (Hymenoptera, Chalcidoidea, Eurytomidae), развивающиеся в семенах некоторых крестоцветных - Зерова, M.Д. (Вестник зоологии, 1981)
A new for science species of chalcids-eurytomids, Eurytoma crambicola sp. n., is described. It was bred from seeds of the Central Asian representative of Cruciferae, Crambe kotschyana B o i s s. The new species is the closest to Eurytoma crambeae Z e r., but differs from it in more elongated flagellum joints in both sexes, a less convex thorax and a more elongated abdomen. The description of the new species is based on the materials from the Badkhyz reservation (Turkmen SSR). The holotype and paratypes are preserved in the collection of the Institute of Zoology of the Ukr. SSR Academy of Sciences (Kiev).